2020
DOI: 10.31258/ijesh.2.1.65-77
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical and Non-physical Investments of Government Expenditure in Education and Health Sectors on Human Development Index in Pekanbaru City

Abstract: In this current globalization era, human resources investment is necessary for each country to improve the index of human development and economic growth, many countries have succeeded in economic growth by relying on human resources despite not having abundant natural resources. However, the success of resource investment is also strongly influenced by the availability of supporting facilities and infrastructure. Based on data of physical and non-physical investments of government expenditure in education and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…It was determined that DAK non-physical contributed to human development from an education sector (HLS) in Riau. The results of this study were consistent with previous research by Fatria et al (2020), which demonstrated that DAK Non-Physical in the education field will impact the HDI, particularly education. Letelier S and Ormeño C (2018) added that fiscal decentralization will influence improving the quality of education.…”
Section: The Effect Of Fiscal Balance Funds On Human Development From Ansupporting
confidence: 92%
See 2 more Smart Citations
“…It was determined that DAK non-physical contributed to human development from an education sector (HLS) in Riau. The results of this study were consistent with previous research by Fatria et al (2020), which demonstrated that DAK Non-Physical in the education field will impact the HDI, particularly education. Letelier S and Ormeño C (2018) added that fiscal decentralization will influence improving the quality of education.…”
Section: The Effect Of Fiscal Balance Funds On Human Development From Ansupporting
confidence: 92%
“…Research by Arifin and Setiawati (2023) and Sandjaja et al (2020), which indicated that special allocation funds (DAK) affect the HDI, supports the conclusions of this study. Human development from a health aspect can be influenced by DAK Physical (Fatria et al, 2020;Nawawi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Nguyen et al (2018), government support takes the form of tax exemptions, tax reductions, and loans with preferential interest rates, as well as trade activities, personnel training, and technology. Thus, government support is crucial not only for the business sector but also for other sectors such as education and health (Fatria et al, 2020).…”
Section: Government Support and Mapsmentioning
confidence: 99%